STUDY OF PHYSICAL AND MECHANICAL PROPERTIES OF SILK FABRICS AND THEIR ANALYSIS (Innovative Technologica: Methodical Research Journal, 2021)
Silk fabrics were selected to create new models of women's blouses, and their composition, physical and mechanical, as well as hygienic properties, were studied in the research laboratory and production facility of the Institute. The analysis of the results of experiments on the choice of fabric for the blouse showed that the physical, mechanical and hygienic characteristics of the selected materials fully meet the requirements of the consumer on all parameters.